Impact of retrograde intrarenal surgery, miniaturized percutaneous nephrolithotomy, and standard percutaneous nephrolithotomy on renal damage biomarkers- A cross-sectional study. - Raj, R. Sachin; Jumde, Suvit (Student's Journal of Health Research Africa, 2025)
Background A frequent urological illness that has a significant socioeconomic burden and a high recurrence rate is nephrolithiasis. With endourological operations being the standard of care, choosing the right treatment is crucial. Patients with nephrolithiasis can find relief from these big stones by undergoing Percutaneous Nephrolithotomy (PCNL), a well-established, minimally invasive surgical treatment. Objectives- The purpose of the study was to assess how biomarkers of renal injury were affected by standard PCNL, miniature PCNL, and retrograde intrarenal surgery. Materials and methods It was a cross-sectional study. The study was carried out in the Department of Urology, Mahatma Gandhi Medical College and Research Institute, Puducherry, India. The study was conducted for one and a half years, that is, from October 2022 to April 2024. In all, 40 patients were enrolled. Participants have to be patients who had undergone PCNL for renal calculus at Mahatma Gandhi Medical College and Research Institute in Puducherry between 2022 and 2024. Results 29 (72.5%) of participants were male, while the other 11 (27.5%) of the participants were female in the study. There were 22 stones on the left side (55%) compared to 18 on the right (45%). Thirty-three (82.5%) patients had sterile urine cultures, while seven (17.5%) had positive urine cultures. Serum Creatinine was found to be 1.14 ± 0.42 mg/dL. Renal parenchymal thickness of the operated kidney was found to be 16.07±1.04 mm, while that of the opposite kidney was 16.07±0.95 mm. Conclusion Urolithiasis is a complex illness that is impacted by several metabolic and clinical risk factors. Recommendations To validate these results, larger trials with longer follow-up are required. It is recommended to include more sensitive kidney biomarkers and standardize surgical factors.